Fabrication of Co1-xFe2+xO4 thick films by screen printing method - Huang, Chongxin. (2009)
Cobalt Oxide and Iron (III) Oxide are mixed together and through dry milling process to synthesize Cobalt Ferrite Oxide (CoFe2O4) powder needed for the fabrication of thick films. Cobalt Ferrite Oxide (CFO), a well-known hard magnetic material is one of the candidates used for high-density recording media. It has a high coercivity and moderate saturation magnetization, a remarkable chemical stability and a mechanical hardness, which are necessary for high-density recording media. Thick films with thickness of around 50μm are fabricated on alumina substrate and fired at temperatures of 800°C to 1100°C using a vertical furnace. The technique employ to fabricate the thick films will be via screen printing, as this will be the most efficient way to achieve films with larger thickness at a relatively shorter time. Structural and magnetic properties of the screen printed thick films were investigated using X-Ray Diffractometer (XRD), Scanning Electron Microscope (SEM) and Vibrating Sample Magnetometer (VSM). In addition to the project, method like spin coating is also studied to understand the benefits to the screen printed thick films. Screen printed films are spin coated with two layers of prepared CFO sol – gel. The magnetic properties of these spin coated thick films are characterized and compared to screen printed films. Furthermore, CFO/PZT multiferroic composite thick films are also fabricated using screen printing method. PZT, also known as Lead Zirconate Titanate, are mixed with CFO in a mass ratio of 10:1. Substantial amount of organic vehicle is mixed together with the powders and roll milled into thixotropic paste. The microstructures, ferroelectric, ferromagnetic properties of the composite thick films will be analyzed.